2017
DOI: 10.1186/s12978-017-0376-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of risky sexual practice in Ethiopia: Systematic review and Meta-analysis

Abstract: BackgroundRisky sexual practice is a major public health problem in Ethiopia. There are various studies on the prevalence and determinants of risky sexual practice in different regions of the country but there is no study which shows the national estimate of risky sexual practices in Ethiopia. Therefore, this review was conducted to estimate the national pooled prevalence of risky sexual practice and its risk factors in Ethiopia.MethodsThe Preferred Reporting Items for Systematic Reviews and Meta-Analyses guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 21 publications
7
45
1
2
Order By: Relevance
“…Young people in Ethiopia are at risk of a broad range of Sexual and Reproductive Health (SRH) problems such as unwanted pregnancies, unsafe abortion, pregnancyrelated complications, and sexually transmitted infections [4][5][6][7]. Besides, they have high unmet need for family planning utilization and limited awareness of STI prevention [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Young people in Ethiopia are at risk of a broad range of Sexual and Reproductive Health (SRH) problems such as unwanted pregnancies, unsafe abortion, pregnancyrelated complications, and sexually transmitted infections [4][5][6][7]. Besides, they have high unmet need for family planning utilization and limited awareness of STI prevention [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of risky sexual practice among newly diagnosed HIV-positive people in the study area was lower (15.8%) compared to findings from different studies in other parts of Ethiopia. Risky sexual practices among preparatory school students was 19.6% in Aksum northern Ethiopia, 17 41.62% among university and college students across Ethiopia, 30 42.8% in the general population of Ethiopia 28 and 22.4% among preparatory school students in Arba Minch town, southern Ethiopia. 16 The differences of the findings may be due to the different characteristics of the study participants.…”
Section: Discussionmentioning
confidence: 96%
“…Factors associated with risky sexual practice in various studies include being educated, being wealthy and young, 27 substance abuse, peer pressure, and watching pornography. 16 , 17 , 28 – 30 Other factors are living in urban areas, 27 being single and married compared to widowed, 19 having HIV-positive sexual partner, nondisclosure of HIV-positive status, having experienced HIV-related stigma, 31 history of suicide attempt and sexual assault. 29…”
Section: Introductionmentioning
confidence: 99%
“…Young people in Ethiopia are at risk of a broad range of sexual and reproductive health (SRH) problems, such as unwanted pregnancy, unsafe abortion, pregnancy-related complications, and STIs. 14 – 17 They also have high unmet needs for family-planning utilization and limited awareness of STI prevention. 17 , 18 Although Ethiopia ihas been registered as one of the lowest HIV-prevalence countries in East Africa, 19 recent reports have indicated that the incidence is rising again.…”
Section: Introductionmentioning
confidence: 99%